Suicide Prevention for LGBT Students1. Issue 141 (22nd March 2013) - Johnson, R. Bradley; Oxendine, Symphony; Taub, Deborah J.; Robertson, Jason
Abstract: This chapter explores the intersection of mental health concerns and suicide of LGBT college students on campus, including bullying and cyberbullying. One campus's approach to providing support for these students is discussed.